Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.4049/jimmunol.180.10.6954
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor-4 Modulates Survival by Induction of Left Ventricular Remodeling after Myocardial Infarction in Mice

Abstract: Left ventricular (LV) remodeling is known to contribute to morbidity and mortality after myocardial infarction (MI). Because LV remodeling is strongly associated with an inflammatory response, we investigated whether or not TLR-4 influences LV remodeling and survival in a mice model of MI. Six days after MI induction, TLR4 knockout (KO)-MI mice showed improved LV function 32 and reduced LV remodeling as indexed by reduced levels of atrial natriuretic factor and total collagen as well as by a reduced heart weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 114 publications
(74 citation statements)
references
References 53 publications
1
67
1
2
Order By: Relevance
“…This proinflammatory response included complement initiation, neutrophil infiltration, and ROS generation 23. TLR‐4–deficient mice exhibited a smaller infarct size with suppression of inflammatory reactions and less adverse remodeling following MI 31. However, the trigger of this response is unknown, and it is also not clear what activated TLR4 signaling after MI.…”
Section: Discussionmentioning
confidence: 99%
“…This proinflammatory response included complement initiation, neutrophil infiltration, and ROS generation 23. TLR‐4–deficient mice exhibited a smaller infarct size with suppression of inflammatory reactions and less adverse remodeling following MI 31. However, the trigger of this response is unknown, and it is also not clear what activated TLR4 signaling after MI.…”
Section: Discussionmentioning
confidence: 99%
“…TLR4 is expressed in the heart and is markedly induced in mouse and rat infarcts and in samples obtained from cardiomyopathic hearts [16]. Recent investigations demonstrated that TLR4 deficient mice have decreased infarct size and suppressed inflammation [17], and exhibit attenuated adverse remodeling following myocardial infarction [18], identifying TLR4 as a key component of the innate immune response in the infarcted heart. In contrast, TLR2 null animals had similar infarct size and comparable inflammatory leukocyte infiltration with their wildtype littermates, but exhibited decreased fibrosis in the non-infarcted area and attenuated postinfarction ventricular remodeling [19].…”
Section: Tlr-mediated Pathwaysmentioning
confidence: 99%
“…Therefore, the possibility that a potential MI size reduction in TLR2 Ϫ/Ϫ mice compared with WT mice may contribute to the attenuated myocardial remodeling in TLR2 Ϫ/Ϫ animals needs to be ruled out. In a similar model of postinfarction remodeling, TLR4 was found to modulate survival as well as LV remodeling after ischemic injury (125,149). Although an enhanced JNK expression has been implicated as a possible intracellular mechanism for the attenuated LV remodeling in TLR4 Ϫ/Ϫ mice (125), the exact mechanisms as to how TLR2 and TLR4 signaling is initiated during myocardial ischemia and how they modulate subsequent ventricular remodeling remain elusive.…”
Section: Tlr Signaling Mediates Myocardial I/r Injurymentioning
confidence: 99%